Phenomenological and microstructural analysis of intermediate temperatures creep in a Ni–Fe-based alloy for advanced ultra-supercritical fossil power plants. (1st January 2016) - Sun, F.; Gu, Y.F.; Yan, J.B.; Zhong, Z.H.; Yuyama, M.
Abstract: A newly developed Ni–Fe-based alloy with high-creep strength and low cost has been developed and evaluated as the promising candidate boiler materials for 700 °C advanced ultra-supercritical coal-fired power plants applications. Three electron microscopy characterization methods–scanning electron microscopy and transmission electron microscopy and high-resolution transmission electron microscopy–were combined to obtain new insights into the microstructural and fracture surface characteristics after creep rupture tests at intermediate temperatures. The alloying elements distribution characteristics have been investigated at nanoscale through EDS mapping, especially Fe element. Fractographic analysis has been also conducted with the finding that the fracture mechanism of the crept specimens at 700 °C/300 MPa and 750 °C/150 MPa are intergranular fracture model. Dislocation configurations resulting from the creep deformation have been also performed on the crept specimens. At 700 °C/300 MPa, Orowan process combining climb of a/2 <110> matrix dislocations was dominant mechanism. At 750 °C/150 MPa, the dominant mechanism is Orowan process combining slip of a/2 <110> matrix dislocations and γ′ precipitates shearing. The formation α-Cr precipitation during the creep process could act as obstacle to impede the dislocation gliding and thus increase the creep strength. Graphical abstract: